Effectiveness of cyclosporine and mycophenolate mofetil in a child with refractory evans syndrome - Farruggia, Piero (PAGEPress Publications, 2011)
Evans Syndrome is a rare autoimmune disease consisting of hemolytic anemia, thrombocytopenia and/or neutropenia. It may be associated with other autoimmune or lymphoproliferative diseases. Its course can be extremely serious and, rarely, even life-threatening; thus it represents a excellent treatment challenge for the pediatric hematologist. First line treatment consists of steroids and/or immunoglobulin; further therapy with rituximab, vincristine, cyclophosphamide and other immunosuppressive drugs can be considered in unresponsive patients. We describe a baby with refractory Evans Syndrome that was cured by prolonged administration of mycophenolate mofetil and remained disease-free for 4 years after the discontinuation of treatment.